1989
DOI: 10.1136/thx.44.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ranitidine treatment on patients with asthma and a history of gastro-oesophageal reflux: a double blind crossover study.

Abstract: Forty eight patients with moderate to severe asthma were enrolled in a double blind crossover study designed to evaluate the effects of ranitidine treatment, 150 mg twice daily for four weeks, on gastro-oesophageal reflux, asthma control, and bronchial reactivity. All 48 had a history of reflux symptoms and 27 had in addition reflux associated respiratory symptoms. Thirty two patients had objective evidence ofacid reflux on 24 hour pH monitoring (pH ofless than 4 for more than I % of the 24 hours) and 27 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 21 publications
0
46
1
Order By: Relevance
“…Relationship between treatment of GERD and asthma outcomes Initial studies focused on the effects of treatment of GERD on asthma outcomes revealed inconsistent results, but in general seemed to suggest an overall improvement in some asthma symptoms [Kiljander et al 1999;Boeree et al 1998;Levin et al 1998;Teichtahl et al 1996;Ford et al 1994;Meier et al 1994;Gustafsson et al 1992;Larrain et al 1991;Ekstrom et al 1989;Nagel et al 1988;Goodall et al 1981;Kjellen et al 1981]. These data resulted in recommendations by the National Asthma Education and Prevention Program's Expert Panel Report 3 (EPR-3) that 'gastroesophageal reflux treatment may benefit patients who have asthma and complain of frequent heartburn or pyrosis, particularly those who have frequent nighttime asthma symptoms.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between treatment of GERD and asthma outcomes Initial studies focused on the effects of treatment of GERD on asthma outcomes revealed inconsistent results, but in general seemed to suggest an overall improvement in some asthma symptoms [Kiljander et al 1999;Boeree et al 1998;Levin et al 1998;Teichtahl et al 1996;Ford et al 1994;Meier et al 1994;Gustafsson et al 1992;Larrain et al 1991;Ekstrom et al 1989;Nagel et al 1988;Goodall et al 1981;Kjellen et al 1981]. These data resulted in recommendations by the National Asthma Education and Prevention Program's Expert Panel Report 3 (EPR-3) that 'gastroesophageal reflux treatment may benefit patients who have asthma and complain of frequent heartburn or pyrosis, particularly those who have frequent nighttime asthma symptoms.…”
Section: Pathogenesismentioning
confidence: 99%
“…The analysis included 12 randomized controlled trials with a combined total of 432 subjects in whom the effects of GERD therapy on asthma outcomes were reported [Kiljander et al 1999;Boeree et al 1998;Levin et al 1998;Teichtahl et al 1996;Ford et al 1994;Meier et al 1994;Gustafsson et al 1992;Larrain et al 1991;Ekstrom et al 1989;Nagel et al 1988;Goodall et al 1981;Kjellen et al 1981]. Treatment with antireflux therapy did not consistently improve any one measure of pulmonary function in patients with asthma, but some studies did report objective improvement in single measurements of lung function such as FEV1 [Meier et al 1994;Larrain et al 1981], morning peak expiratory flow rates (PEF) [Levin et al 1998] and evening PEF [Teichtahl et al 1996;Goodall et al 1981].…”
Section: Pathogenesismentioning
confidence: 99%
“…There have been many studies dealing with asthma outcome and medical anti-reflux therapy. Field and Sutherland (1998) reviewed the previously published data on medical anti-reflux therapy with H 2 -receptor blockers (H 2 blockers), cimetidine (Goodall et al 1981;Larrain et al 1991) and ranitidine (Harper et al 1987;Nagel et al 1988;Ekstrom et al 1989;Gustaffson et al 1992), and with a proton pump inhibitor (PPI) omeprazole (Ford et al 1994;Meier et al 1994;Harding et al 1996;Teichtahl et al 1996), showing that asthma symptoms were improved. Kiljander (2003) suggested that, in the management of GERD-related asthma, PPIs other than omeprazole should be used at double the standard dose.…”
mentioning
confidence: 99%
“…However, such treatment, even with H 2 blockers which effectively reduce gastric pH and nocturnal acid secretion, has shown only a small improvement in asthma symptoms, with a 15% improvement in nocturnal scores and a 10% reduction in bronchodilator use [35]. The dose of H 2 blocker was modest in each case, which may explain the relative lack of effect.…”
Section: Treatment Of Gor In the Presence Of Asthmamentioning
confidence: 67%